Frequency to Non-Compliance to Oral Iron Therapy in Pregnancy and Common Factors Leading to it - qureshi, Qandeela irum; Hashmi, Basit; Ammar, Ahmed Siddique; Khattak, Shehrbano; Saeed, Sahar; Alavi, Hirra (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: The objective of this study was to determine frequency of non-compliance to oral iron therapy in pregnancy and common factors leading to it. METHODOLOGY: It was a cross-sectional study done in the Department of Obstetrics and Gynecology of Lady Willington Hospital Lahore, Pakistan. The duration of this study was six months i.e., 3rd October 2019 to 2nd March 2020. All antenatal patients between ages of 18 to 45 years presented in the obstetrics outdoors or admitted in the ward were included in this study. A total of 245 patients were included in this study by consecutive non-probability sampling. Patients with gynecological problems, patients dependent on others for their medication cost, patients with psychiatric illness or physical disability were excluded. Post stratification Chi-square test was applied keeping P-value ≤0.05 as significant RESULTS: Among 245 patients, mean age was 27±2.16 years. Iron supplement used by 245 patients was analyzed as 159 (65%) patients had used the iron supplement while 86 (35%) patients didn’t use iron supplements (P-value 0.001). Iron supplement used by 245 patients was analyzed and only 93 (38%) patients had used the iron supplement while 152 (62%) patients didn’t use iron supplements. CONCLUSION: The coverage of antenatal iron and folic acid supplements is very low in the surveyed districts of Pakistan due to lack of parental education and older aged women belonging to poor households.